SAT0397 Serum Apolipoprotein B is Associated with Increased Risk of the Presence and Progression of Carotid Atherosclerosis in Patients with Psoriatic Arthritis. (10th June 2014) - Tam, L.-S.; Shang, Q.; Li, E.; Wong, P.; Zhu, T.; Li, T.; Pui, M.; Leung, K.; Kun, E.; Yu, C.-M.
Abstract : Background: Risk factors that are associated with a higher risk of subclinical atherosclerosis (SCA) in psoriatic arthritis (PsA) have never been examined in longitudinal studies. Objectives: The aim of this study is to examine the progression of SCA in patients with PsA, and to identify risk factors associated with the development of atherosclerotic plague for this patient population. Methods: 81 PsA patients participated in this prospective cohort study. All patients underwent carotid ultrasonography at 2 time points separated by a mean ± SD of 78±7 months. The longitudinal presence of carotid plaque and intima-media thickness (IMT) were measured at baseline and follow up. The associations of baseline clinical and demographic parameters, and cardiovascular risk factors with the presence of baseline or progressive plaque, were explored. Results: In total, 38 out of 81 (46.9%) of PsA patients demonstrated ≥1 carotid plaque on the baseline or follow up ultrasound. At the follow up ultrasound, 23/81 (28.4%) patients had plaque progression (new plaque, incidence rate 4.37 per 100 person-years), while 12/81 (14.8%) patients had stable plaque (plaque at baseline and follow up). Three patients (3.7%) had plaque regression (plaque at baseline but no plaque at follow up). Univariate analysis revealed that the following variables were associated with carotid plaque with a p-value of <0.1 (table 1 ): older age, older age at PsA and psoriasis diagnosis, longer disease duration, increased fasting sugar, total cholesterol and apolipoprotein (Apo) B levels. Other traditional CV risk factors including blood pressure, body mass index, waist hip ratio, high density lipoprotein (HDL)- cholesterol (C), low density lipoprotein (LDL)-C, Apo A1 and insulin level and Framingham risk score; disease related parameters including number of tender and swollen joints, ESR, hsCRP, whether patient achieved minimal disease activity and novel cytokines (interleukin [IL]-33, soluble ST2, IL-17 and IL-23) levels were not associated with the presence of plaque. All of the potential explanatory variables with p<0.1 in the univariate analysis were analyzed using logistic regression. Independent explanatory variables associated with the presence of baseline or progressive plaque in PsA patients included older age (OR 1.071, 95% CI 1.007–1.140, P =0.03) and increased Apo B levels (OR 1.056, 95% CI 1.013–1.101, P =0.01). Conclusions: High Apo B level confers an increased risk of the presence of any current, progressive or acquired carotid plaque in PsA patients even after adjusting for age and other traditional CV risk factors. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3137